Pengaruh Trainee terhadap Kinerja Karyawan di Unit Front Office di Hotel X Ancol Jakarta - Yuliana, Yuliana (Bina Nusantara University, 2011)
Front office (FO) is the poster image of a hotel. That is because this part of the first to welcome guests and can be regarded as the image of the hotel. Therefore, the officer who was in the front office should be able to serve guests with the best service so the guest will satisfaction can be realized and the image is formed with a good hotel. The existence of the front office as an image other than the hotel, as well as the information center. Customers only know part of this front office that can provide all the information you need, be it a hotel facilities as well as all information related to guest attractions such as location, schedule a show or concert. Hence, a front office staff should be kept up to date on the information circumstances surrounding the hotel and also the hotel. Officers in the unit front office should be able to well communicate and able to provide the needed of the guest. Because of limited number of employees, the trainees are very instrumental in petrified duties and responsibilities in the front office. Its presence will bring influence to the performance of employees in the front office.Â